2017
DOI: 10.1007/s00270-016-1544-6
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Ultrasonography-Guided Percutaneous Radiofrequency Ablation in Hyperparathyroid Patients in Whom Surgery Is Not Feasible

Abstract: Although this is a limited case series, it demonstrates the potential feasibility of RFA for HPT. Benefits were achieved particularly in patients with small parathyroid lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Recent studies have reported the potential efficacies of these approaches: the complete remission rate may reach 86.7% with a mean follow-up duration of 12 months (10). Thus far, RFA has been reported in limited numbers of patients (1-9 patients per study) (6)(7)(8)(9). In our study, among the 11 patients treated, complete disappearance of the nodule and biochemical remission were reported in seven patients (63.6%).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Recent studies have reported the potential efficacies of these approaches: the complete remission rate may reach 86.7% with a mean follow-up duration of 12 months (10). Thus far, RFA has been reported in limited numbers of patients (1-9 patients per study) (6)(7)(8)(9). In our study, among the 11 patients treated, complete disappearance of the nodule and biochemical remission were reported in seven patients (63.6%).…”
Section: Discussionmentioning
confidence: 44%
“…Three radiologists, who had 22, 19, and 14 years of clinical experience, respectively, in performing and evaluating neck US images, performed all US examinations with one of the three US systems: an iU22 ultrasound machine (Philips Healthcare), an RS 80 (Samsung Medison Co., Ltd.), or an EUB-7500 HV (Hitachi Medical Systems). All three US systems were equipped with a high-frequency linear probe (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The index nodule volume was calculated as V = πabc/6, where V is the volume, a is the largest diameter, and b and c are the other two perpendicular diameters.…”
Section: Preprocedural Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to surgical treatment, local ablation remains to be a relatively simple procedure, easily tolerant for patients, with fewer complications, a shorter hospitalization and convalescence period [23]. After more than a decade of clinical application since the first publication by Bennedbaek et al [24], thermal ablation technique has been demonstrated to be effective to destroy parathyroid gland tissue and normalize serum PTH and calcium [25][26][27][28][29][30][31]. Nevertheless, no comprehensive review of thermal ablation in the treatment of PHPT has been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports and case series have been published. Percutaneous injection of ethanol [21,22], acetic acid [23] and calcitriol [24] and thermal ablation, including radiofrequency (RF) [25,26], laser [27] and high-intensity focussed ultrasound (HIFU) [28,29], have been assessed in patients with hyperparathyroidism. A preliminary study by our group also confirmed that ultrasound-guided MWA was safe and effective in destroying parathyroid gland tissue in patients with SHPT [15,16].…”
Section: Discussionmentioning
confidence: 99%